The Influence of Effective Communication, Teacher Performance in Improving the Quality of Learning in Private Junior High Schools in Jakabaring District, Palembang City - Chintia, Jenny; Widayatsih, Tri; Indrawati, Sri Wahyu (Universitas Pahlawan Tuanku Tambusai, 2025)
The quality of education in Indonesia is still a concern, despite various reform efforts that have been made. One of the main challenges is ineffective communication in schools, which has an impact on low teacher performance and learning quality. This study aims to analyze the influence of effective communication and teacher performance on the quality of learning in Private Junior High Schools in Jakabaring District, Palembang City. Effective communication between teachers and students is considered the key to creating a conducive learning atmosphere, while teacher performance which includes competence, creativity and professionalism has an important role in determining student learning outcomes. A quantitative approach was used in this study involving 8 junior high schools. Private sector in Jakabaring District as the object of study. Data were collected through surveys and analyzed to see a significant relationship between effective communication, teacher performance and learning quality. The results showed that effective communication had a significant influence on the quality of learning which showed that the calculated t value of 3.648 was greater than the t-value of the table of 2.021 with the degree of freedom or df=40. Looking at the testing criteria, it is said that it is rejected and accepted . The same score also shows a significant number on the influence of teacher performance on the quality of learning , namely the calculated t value of 8.163 which is greater than the t table of 2.021 with a degree of freedom of 40. so it is rejected and accepted. Simultaneously, effective communication and teacher performance make a significant contribution to the quality of learning, showing a synergistic relationship between the two. Judging by the value of F, the calculation is greater than the F of the table, which is 37.432 3.24 and the significance value is 0.000 0.005 so that it can be said H0 to be rejected and Ha accepted.